The influence of restricted food supplies on the development of larvae and on the fecundity of Palembus dermestoides fairn. (Tenebrionidae) - Tock, Hing Chua; Rajini Chandrapal (Pergamon, 1978)
The effects of the amounts of food available to larvae and to adults were investigated in Palembus dermestoides Fairn. The quantities provided for larvae were 1, 2, 5, 10 mg/larva/week but these were raised to 100 mg/pair/week when adults emerged, and those for the adults were 20, 50, 100, 200, 400 and 1000 mg/pair/week. Scarcity of food prolonged the larval developmental period, increased instar number, increased mortality, prolonged the preovisposition period and reduced future fecundity. The adults given little food also laid fewer eggs.